G-Protein-Coupled Estrogen Receptor (GPER)-Specific Agonist G1 Induces ER Stress Leading to Cell Death in MCF-7 Cells - Vo, Diep-Khanh Ho (Biomolecules, 2019)
The G-protein-coupled estrogen receptor (GPER) mediates rapid non-genomic effects of estrogen. Although GPER is able to induce proliferation, it is down-regulated in breast, ovarian and colorectal cancer. During cancer progression, high expression levels of GPER are favorable for patients’ survival. The GPER-specific agonist G1 leads to an inhibition of cell proliferation and an elevated level of intracellular calcium (Ca(2+)). The purpose of this study is to elucidate the mechanism of G1-induced cell death by focusing on the connection between G1-induced Ca(2+) depletion and endoplasmic reticulum (ER) stress in the estrogen receptor positive breast cancer cell line MCF-7. We found that G1-induced ER Ca(2+) efflux led to the activation of the unfolded protein response (UPR), indicated by the phosphorylation of IRE1α and PERK and the cleavage of ATF6. The pro-survival UPR signaling was activated via up-regulation of the ER chaperon protein GRP78 and translational attenuation indicated by eIF2-α phosphorylation. However, the accompanying pro-death UPR signaling is profoundly activated and responsible for ER stress-induced cell death. Mechanistically, PERK-phosphorylation-induced JNK-phosphorylation and IRE1α-phosphorylation, which further triggered CAMKII-phosphorylation, are both implicated in G1-induced cell death. Our study indicates that loss of ER Ca(2+) is responsible for G1-induced cell death via the pro-death UPR signaling.